The Extracellular Matrix and Neuroblastoma Cell Communication—A Complex Interplay and Its Therapeutic Implications - Irena Horwacik (Cells, 2022)
Neuroblastoma (NB) is a pediatric neuroendocrine neoplasm. It arises from the sympatho-adrenal lineage of neural-crest-derived multipotent progenitor cells that fail to differentiate. NB is the most common extracranial tumor in children, and it manifests undisputed heterogeneity. Unsatisfactory outcomes of high-risk (HR) NB patients call for more research to further inter-relate treatment and molecular features of the disease. In this regard, it is well established that in the tumor microenvironment (TME), malignant cells are engaged in complex and dynamic interactions with the extracellular matrix (ECM) and stromal cells. The ECM can be a source of both pro- and anti-tumorigenic factors to regulate tumor cell fate, such as survival, proliferation, and resistance to therapy. Moreover, the ECM composition, organization, and resulting signaling networks are vastly remodeled during tumor progression and metastasis. This review mainly focuses on the molecular mechanisms and effects of interactions of selected ECM components with their receptors on neuroblastoma cells. Additionally, it describes roles of enzymes modifying and degrading ECM in NB. Finally, the article gives examples on how the knowledge is exploited for prognosis and to yield new treatment options for NB patients.